El regalo de la Pachamama - Matsushita, Toshi (Dolphin Productions, 2008)
Kunturi is a 13-year-old boy who lives a traditional existence until his grandmother dies and his father takes him on his first llama caravan. For three months, Kunturi traveled the Ruta de la Sal, exchanging blocks of salt for Andean products. In his final destination, Kunturi's life changes forever when he meets the beautiful Ulala. They both feel the air of romance when they discover they share the same dream. --